Ageing population and Spanish pension system reforms: Effects on average pensions and inequality among pensioners - Pablo de Pedraza; Rafael Mu\~noz de Bustillo; Luis Alberto Rivas (Colegio de Economistas de A Coru\~na, 2009)
An ageing population is prompting the reform of pension systems. The Spanish pension system has undergone two consecutive reforms and a third one is currently being taking into consideration. All three involve the lengthening of the period used to calculate the size of pensions. This paper offers an estimate of the impact of each system on average pensions and inequality among pensioners. The paper also explores the applicability of the conclusions to the generation of workers now in the middle of their working life, that is considering the characteristics of new working lives.
Keywords: 330; Ageing population; pension system reform; spain; Alternde Bevölkerung; Gesetzliche Rentenversicherung; Spanien